Measurement of nasal potential difference in young children with an equivocal sweat test following newborn screening for cystic fibrosis. Issue 6 (3rd June 2010) - Sermet-Gaudelus, Isabelle; Girodon, Emmanuelle; Roussel, Delphine; Deneuville, Eric; Bui, Stéphanie; Huet, Frédéric; Guillot, Marcel; Aboutaam, Rola; Renouil, Michel; Munck, Anne; des Georges, Marie; Iron, Albert; et al.
Abstract : Background: A challenging problem arising from cystic fibrosis (CF) newborn screening is the significant number of infants with hypertrypsinaemia (HIRT) with sweat chloride levels in the intermediate range and only one or no identified CF-causing mutations. Objectives: To investigate the diagnostic value for CF of assessing CF transmembrane conductance regulator (CFTR) protein function by measuring nasal potential difference in children with HIRT. Methods: A specially designed protocol was used to assess nasal potential difference (NPD) in 23 young children with HIRT (3 months–4 years) with inconclusive neonatal screening. Results were analysed with a composite score including CFTR-dependent sodium and chloride secretion. Results were correlated with genotype after extensive genetic screening and with clinical phenotype at follow-up 3 years later. Results: NPD was interpretable for 21 children with HIRT: 13 had NPD composite scores in the CF range. All 13 were finally found to carry two CFTR mutations. At follow-up, nine had developed a chronic pulmonary disease consistent with a CF diagnosis. The sweat test could be repeated in nine children, and six had sweat chloride values ≥60 mmol/l. Of the eight children with normal NPD scores, only two had two CFTR mutations, both wide-spectrum mutations. None had developed a CF-like lung disease at follow-up. The sweat test could be reassessed in five of these eight children and all had sweat chloride values <60 mmol/l. CF diagnosis was ruled out in six of these eight children. Conclusion: Evaluation of CFTR function in the nasal epithelium of young children with inconclusive results at CF newborn screening is a useful diagnostic tool for CF.